TANGGUNG JAWAB LINGKUNGAN, PERTUMBUHAN DAN SIKLUS HIDUP PERUSAHAAN TERHADAP CASH HOLDING PADA PERUSAHAAN MANUFAKTUR DI INDONESIA - Andi Aditya Hardinto; Juniati Gunawan; Idrianita Anis (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2022)
The research examines the effect of environmental responsibility, growth and company life cycle on cash holding - This study uses secondary data in the annual report of manufacturing companies obtained through the official website of the Indonesia Stock Exchange (www.idx.co.id) , a sustainability report that can be obtained through the company's website and GRI-Database during the 2018-2020 period with a total sample of 195 samples. Multiple linear regression analysis can be concluded that environmental responsibility has a negative effect on cash holding, growth has a positive effect on cash holding and the company's life cycle in a stagnant stage has a positive effect on cash holding.